Culture as infrastructure in learning health systems - Alexandra H. Vinson (Wiley, 2021)
Abstract Building Learning Health Systems requires the combination of information, regulatory, and cultural infrastructures that create communities focused on changing health outcomes through the application of quality improvement methodology, focused data collection, closed feedback loops, and community‐participatory techniques. Accomplishing the vision of the Learning Health System relies on building robust infrastructures, and teaching a wide variety of stakeholders to participate in these novel socio‐technical systems. In this commentary, I draw on empirical examples from fieldwork with Learning Networks to describe how social scientists view culture and what this concept might hold for learning health sciences.